Rising Above the Challenge : The Underutilization of Data Analysts and Engineers - Deepak Chanda, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Unfortunately, this often means that data analysts and data engineers are underutilized in many organizations — their skills go largely untapped trying to solve strategic business challenges. However, they often note inefficiencies and take the lead on innovation. This article deploys a real-world case study to investigate the phenomenon, exploring how a data-professional at a company, went above and beyond to secure meaningful transformation to the organization.
Keywords: Data Analysts; Data AnalystsUnderutilized; Innovation; Transformation